When phytoplankton do not bloom: the case of the dinoflagellate Lepidodinium chlorophorum in southern Brittany (France) assessed by environmental DNA. (March 2023) - Roux, Pauline; Schapira, Mathilde; Mertens, Kenneth Neil; André, Coralie; Terre-Terrillon, Aouregan; Schmitt, Anne; Manach, Soazig; Collin, Karine; Serghine, Joelle; Noel, Cyril; Siano, Raffaele
Highlights: Rare Lepidodinium eDNA was detected during unfavourable growth seasons. Increase in Lepidodinium was correlated with ammonium pulse from sediment. No cysts of Lepidodinium were identified in the sediments. Temporary pelagic stage during non-blooming phase may explain species overwintering. Abstract: Green seawater discolorations caused by the marine dinoflagellate Lepidodinium chlorophorum are frequently observed during summer along southern Brittany coasts (NE Atlantic, France). Here, the ecology of L. chlorophorum is studied during a non-bloom period using high-throughput sequencing metabarcoding of environmental DNA (eDNA) samples for the detection of this species at low concentrations. Sediment samples (for metabarcoding and cyst analyses) were collected in January–February 2019 and water samples from two stations were collected at three water depths in September–March 2019–2020 and 2020–2021 (for metabarcoding and environmental parameters). The protistan community was dominated by dinoflagellates and was homogenous in the water column. Amplicon sequence variants (ASVs) associated with the genus Lepidodinium were detected in autumn–winter at low relative abundances (minimum: 0.01%). Increases in Lepidodinium abundance were positively correlated with pulses of ammonium re-suspended from bottom sediments. Although Lepidodinium eDNA (<1%) was detected in the sediments, no cyst morphotypes could be associated with Lepidodinium, and germination experiments revealed no Lepidodinium -like cells, leaving in doubt the existence of resting cysts of this species in the seed bank. It is hypothesised that temporary Lepidodinium cells remained present in the water column at low concentrations during the autumn–winter period, awaiting ammonium input from sediments to initiate growth, and that blooms develop when water column stratification and river input provide favourable environmental conditions for biomass increases.